EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN PEDIATRI PENYAKIT DIARE DI INSTALASI RAWAT INAP RSU KOTA TANGERANG SELATAN - Andriyani Rahmah Fahriati (PHRASE (Pharmaceutical Science) Journal, 2022)
Diarrhea is the second leading cause of death in children under five years of age and was responsible for the deaths of 370,000 childrens in 2019. Microorganisms that cause diarrhea tend to be caused by bacterial infections. Therefore, antibiotics can be used as first-line therapy for treating cases of diarrhea. The increasing prevalence of antibiotic use in pediatric patients with diarrhea requires appropriate therapy to reduce morbidity. One aspect related to this is the evaluation of the rationality of the use of antibiotics. The purpose of this study was to determine the evaluation of the rationality of using antibiotics in pediatric patients with diarrheal disease at the South Tangerang City General Hospital in 2020. This study was non-experimental. Data collection in this study was carried out retrospectively and analyzed descriptively. Obtained data with a total of 37 research samples. The study was conducted by evaluating the rationale for using antibiotics based on the right indication, the right drug, the right dose, the right patient, and the right way of administering the drug. The data obtained were compared with the World Gastroenterology Organization Global Guidelines 2012, ISO 2019, and MIMS edition 17. The results showed that of the 37 patients who suffered the most from diarrhea, aged 0 – 5 years, 29 patients were affected and the sex most affected by diarrhea was behavior. – male with a total of 21 patients. Evaluation of the use of antibiotics or rationality in pediatric patients with the diarrheal disease based on the criteria of 100% right indication, 100% right indication, 100% the right drug, 94,6% the right dose 100%, the right patient, and 100% the right way of administering the drug.